A Unique Quenching and Deformation Dilatometer for Combined In Situ Neutron Diffraction Analysis of Engineering Materials. Issue 11 (22nd November 2021) - Li, Xiaohu; Hofmann, Michael; Landesberger, Martin; Reiberg, Marius; Zhang, Xiao; Huang, Yuanding; Wang, Lijiu; Werner, Ewald; Gan, Weimin
Abstract : A modified quenching and deformation dilatometer is now in operation at the Heinz Maier‐Leibnitz Zentrum neutron center. It is customized for running neutron scattering measurements during the temperature/deformation treatment of the sample, in particular neutron diffraction (phase, texture, lattice strain) and neutron small angle scattering. Further details can be found in the article number 2100163 by Xiaohu Li, Weimin Gan, and co‐workers.